Concave-Convex π-π Template Approach Enables the Synthesis of [10]Cycloparaphenylene-Fullerene [2]Rotaxanes - Xu, Youzhi; Kaur, Ramandeep; Wang, Bingzhe; Minameyer, Martin; Gsänger, Sebastian; Meyer, Bernd; Drewello, Thomas; Guldi, Dirk Michael; Von Delius, Max (Journal of the American Chemical Society, 2018)
The cycloparaphenylenes (CPPs) are a class of strained macrocycles that until 2008 were considered beyond the reach of organic synthesis. With its cyclic array of ten para-substituted phenylene rings, [10]CPP possesses a concave π-system that is perfectly preorganized for the strong supramolecular association of convex fullerenes such as C60. Although mechanically interlocked CPP architectures have been observed in the gas phase, the rational synthesis of bulk quantities has not been achieved yet, which is likely due to the fact that conventional template strategies are not amenable to CPP rings that lack heteroatoms. Here, we report the synthesis of two [2]rotaxanes in which a [10]CPP ring binds to a central fullerene bis-adduct and is prevented from dethreading by the presence of two bulky fullerene hexakis-adduct stoppers. The final step in the rotaxane synthesis is surprisingly efficient (up to ca. 40% yield) and regioselective because the fullerene acts as an efficient convex template, while [10]CPP acts as a supramolecular directing group, steering the reaction at the central fullerene exclusively toward two trans regioisomers. Comprehensive physicochemical studies confirmed the interlocked structure, shed light on the dynamic nature of the CPP-fullerene interaction, and revealed intriguing consequences of the mechanical bond on charge transfer processes. In light of recent advances in the synthesis of nanohoops and nanobelts, our concave-convex π-π templating strategy may be broadly useful and enable applications in molecular electronics or complex molecular machinery.
CRIS-Team Scopus Importer:2022-04-14